Analytical and Numerical Model of Aluminum Alloy Swaging Ring Design to Study the Effect on the Sealing for Piping Systems - Ahmet Atak (Civil Engineering Journal, 2021)
In various fields of engineering, the assembly and repair of hydraulic installations are accomplished by joining the pipes. In such applications, the ring swaging method is used to connect the fittings to the pipes by means of a hydraulic hand tool. The basis to develop a swaging tool relies on the knowledge of the design parameter that influence plastic deformation of the swaging ring. In addition to build control over the design parameters, it is necessary to join pipes under severe conditions such as cryogenic vacuum and constrained space which require an intact sealing. In this study, the effect of swaging ring designs on sealing and strength has been examined and different swaging methods have been investigated by finite element modeling methods. Based on the obtained results, the analysis methodology of ring swaging and the characteristic impact of swaging ring design on the sealing of pipe connection are shown. The prime novelty of the study is to report the impact of swaging ring design and geometry on sealing efficiency of the pipe connection. The results of the study open new avenues for the development of efficient tools for designing swaging rings. Doi: 10.28991/cej-2021-03091641 Full Text: PDF